Livelihood Strategies of Lakeside Household Community around Jatigede Reservoir upon Facing its Rural Transformation - Muslimah Handayani W, Arni
Jatigede Reservoir is an infrastructure that was built in the southeastern part of Sumedang Regency, and is surrounded by 5 Subdistricts namely Cisitu, Darmaraja, Jatinunggal, Wado, and Jatigede Districts. The reservoir has officially operated since 2014 and has led to a transformation in the surrounding villages. By conducting mixed research, the author tries to describe the community livelihood strategies at the edge of the reservoir in the face of village transformation. The research was carried out to achieve 3 targets, namely: 1) Explaining the context of village transformation that occurred at the edge of the Jatigede Reservoir; 2) Explain the community livelihood strategies on the banks of the Jatigede Reservoir, and; 3) Explain the results of community livelihood strategies arround Jatigede Reservoir. Rural transformation has an impact on changes in land use, population, economy, and infrastructure services. The changing of 3,509.14 hectares of productive land as a watershed encouraged the emergence of residential and agricultural areas in the area around the reservoir, where the area was designated as a local protected area. Inundation results in pressure on residential and agricultural areas, thereby driving population movements and weakening the village economy. Village communities who generatively work as farmers experience loss of arable land and opening new agricultural fields on the banks of the reservoir with uncertain productivity. Agricultural productivity in the affected areas has decreased, where agricultural output in Cisitu District has shrunk by 23.38%, Darmaraja District by 61.66%, and Wado by 17.27%. The Jatigede District experienced a decrease in vegetable production by 73.43% and Jatinunggal District experienced a decrease in the fruit yield of 67.25%. As for the inundation of a number of infrastructures, it weakens the capacity of village infrastructure and services so that it depends on the activity centers of the District. The construction of the Jatigede Reservoir is a benchmark for the transformation of the surrounding villages and causes the weakening of people's livelihood assets. Weakened assets include natural, financial, physical and human assets. The assets that are in good condition are social assets, so that even in shock, the community stilliv has the ability to work together in groups. However, the weakness of assets means that people have fewer choices for survival. Even though natural assets are in a weak condition, most community activities still depend on land availability. Communities diversify their livelihoods by collecting natural products, farming, raising livestock, engaging in new economic sectors consisting of tourism and fisheries, utilizing remittances, social assistance, and utilizing social networks. Community efforts to diversify livelihoods result in weak livelihood outcomes with indications of food vulnerability. Most of the people on the banks of the reservoir are farmers and residents in settlements who lose their land and have no expertise other than knowledge related to agriculture and collecting natural products. Where in the beginning the land provided food reserves, produce that could be sold, natural products that could be collected, and provided jobs for the villagers. The loss of land has an impact on the economic collapse of the village, and the ability of the community to fulfill their basic needs. The results of welfare measurement show that 78% of respondents experienced a decrease in income, 84.76% experienced a decrease in work days, 39.05% had difficulty meeting food needs, and 85.71% had disasters that were unsafe. Thus the livelihood strategies of rural communities around Jatigede Reservoir produce low welfare and resilience.